2009
DOI: 10.1123/jsep.31.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Youth Sport Parenting Styles and Practices

Abstract: The purpose of this study was to examine parenting styles and associated parenting practices in youth sport. Following a season-long period of fieldwork, primary data were collected via interviews with 56 parents and supplemented by interviews with 34 of their female children. Data analysis was guided by Grolnick's (2003) theory of parenting styles. Analyses produced five findings: (1) Autonomy-supportive parents provided appropriate structure for their children and allowed them to be involved in decision maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
3
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 44 publications
4
126
3
10
Order By: Relevance
“…Lareau, 2003), a broader approach to the parent-child relationship in sport has emerged, addressing issues such as how parents shift between different roles, such as offering support and giving sport-related advice (Elliott & Drummond, 2015;Knight & Holt, 2014), how parents might either identify with or oppose the sporting culture of their child's team or club (McMahon & Penney, 2014), how family life is restructured when children enter a sport (Dorsch, Smith, & McDonough, 2014) and how parenting styles in sport depend on the child's personality and needs (Holt, Tamminen, Black, Mandigo, & Fox, 2009;Trussell & Shaw, 2012).…”
Section: Studies On Parenting and Sportmentioning
confidence: 99%
“…Lareau, 2003), a broader approach to the parent-child relationship in sport has emerged, addressing issues such as how parents shift between different roles, such as offering support and giving sport-related advice (Elliott & Drummond, 2015;Knight & Holt, 2014), how parents might either identify with or oppose the sporting culture of their child's team or club (McMahon & Penney, 2014), how family life is restructured when children enter a sport (Dorsch, Smith, & McDonough, 2014) and how parenting styles in sport depend on the child's personality and needs (Holt, Tamminen, Black, Mandigo, & Fox, 2009;Trussell & Shaw, 2012).…”
Section: Studies On Parenting and Sportmentioning
confidence: 99%
“…Keegan et al 2009Keegan et al , 2010b); (2) verbal feedback (e.g. Beltman and Volet 2007, Gould et al 2008, Holt et al 2009) -the relatively explicit evaluative communications of coaches, parents and peers, including criticism and praise and also referring to considerations such as timing, publicity (public vs. private); and (3) behavioural reinforcement (e.g. McCarthy and Jones, 2007) -the punishment or rewarding of outcomes, effort, moral behaviour etc.…”
Section: Evaluation Climatementioning
confidence: 99%
“…Regarding autonomy, participants discussed the perceived benefits to children's problem solving ability when parents balance involvement and support while also allowing children appropriate space to be exposed to sport challenges and develop self-regulation. Previous research has found that parents' support of autonomy via the provision of choice and encouragement of decisionmaking is also linked to parental ability to understand children's internal mental experiences [53]. Finally, regarding competence, participants discussed the importance of parents who focus on children's strengths and encourage children to take on sport challenges.…”
Section: Positive Sport Parent Behaviourmentioning
confidence: 99%